Association between Bout Duration of Physical Activity and Health: Systematic Review - Jakicic, John M. (Med Sci Sports Exerc, 2019)
PURPOSE. To conduct a systematic literature review to determine if physical activity episodes of <10 minutes in duration have health-related benefits; or, alternatively, if the benefits are only realized when the duration of physical activity episodes is ≥10 minutes. METHODS. The primary literature search was conducted for the 2018 Physical Activity Guidelines Advisory Committee Report and encompassed literature through June 2017, with an additional literature search conducted to include literature published through March 2018 for inclusion in this systematic review. RESULTS. The literature review identified 29 articles that were pertinent to the research question that used either cross-sectional, prospective cohort, or randomized designs. One prospective cohort study (N=4,840) reported similar associations between moderate-to-vigorous physical activity (MVPA) and all-cause mortality when examined as total MVPA, MVPA in bouts ≥5 minutes in duration, or MVPA in bouts ≥10 minutes in duration. Additional evidence was identified from cross-sectional and prospective studies to support that bouts of physical activity <10 minutes in duration are associated with a variety of health outcomes. Randomized studies only examined bouts of physical activity ≥10 minutes in duration. CONCLUSIONS. The current evidence, from cross-sectional and prospective cohort studies, supports that physical activity of any bout duration is associated with improved health outcomes, which includes all-cause mortality. This may suggest the need for a contemporary paradigm shift in public health recommendations for physical activity, which supports total moderate-to-vigorous physical activity as an important lifestyle behavior regardless of the bout duration.